2017
DOI: 10.1021/acs.cgd.7b01110
|View full text |Cite
|
Sign up to set email alerts
|

Rare Examples of Amine-Templated Organophosphonate Open-Framework Compounds: Combined Role of Metal and Amine for Structure Building

Abstract: By introduction of 2-methyl-1,5-diaminopentane (DAP) and 1,4-diaminobutane (DAB) as templated ions, three new amine-templated organophosphonate open-framework compounds [H2DAP][Zn 6 (Hhedp) 2 (hedp) 2 ]•4H 2 O, I, [H2DAB]-[Zn 6 (Hhedp) 2 (hedp) 2 ]•4H 2 O, II, and [H2DAB][Zn 3 (hedp) 2 ]•2H 2 O, III, have been synthesized, structurally analyzed, and characterized for the first time. Both compounds I and II have analogous 2-D sheet structure connecting through metal and diphosphonates (1-hydroxyethane-1,1-dipho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Coordination networks based on d 10 transition-metal ions are of great importance and have attracted much attention owing to their potential applications when serving as optical function materials. , Therefore, the solid-state photoluminescence properties of compounds 1 – 3 were investigated at ambient temperature (Figure ), and the observed spectra were compared with the spectral data of pure H 4 –HEDP solution. The free diphosphonate molecule exhibits a fluorescence emission band centered at 359 nm upon being excited with UV light (λ ex = 320 nm). , This emission band for diphosphonic acid corresponds to π–π* transitions. Compounds 1 – 3 display a similar emission behavior, and they can emit blue fluorescence emission bands with maxima at 430 nm for 1 , 424 nm for 2 , and 427 nm for 3 , respectively (λ ex = 370 nm).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Coordination networks based on d 10 transition-metal ions are of great importance and have attracted much attention owing to their potential applications when serving as optical function materials. , Therefore, the solid-state photoluminescence properties of compounds 1 – 3 were investigated at ambient temperature (Figure ), and the observed spectra were compared with the spectral data of pure H 4 –HEDP solution. The free diphosphonate molecule exhibits a fluorescence emission band centered at 359 nm upon being excited with UV light (λ ex = 320 nm). , This emission band for diphosphonic acid corresponds to π–π* transitions. Compounds 1 – 3 display a similar emission behavior, and they can emit blue fluorescence emission bands with maxima at 430 nm for 1 , 424 nm for 2 , and 427 nm for 3 , respectively (λ ex = 370 nm).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Considering the similarity between inorganic phosphates (or phosphites) and organophosphonates, the organoamines-directed assembly is also applicable to the metal phosphonate. An overview of literature indicated that the early investigated organoamines mainly focus on the small rigid/flexible species, just exampled by heterocyclic amine and aliphatic amine. By contrast, the long aliphatic amine (the total atoms for the chain larger than eight) and large heterocyclic amine (the N -heterocycle larger than three) are relatively less investigated. This is not surprising for several reasons, one of which may be partly due to the fact that such long-chain flexible organic amines are easily decomposed under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Of late, the advancement of transition-metal-based materials such as oxides, nitrides, sulfides, selenides, hydroxides, phosphides, phosphates, and various composite materials are considered as excellent catalysts for boosting electrochemical water splitting performance by replacing precious platinum/iridium catalysts. The selection of flexible phosphonate groups along with incorporation of variable templated organoamines in hybrid metal phosphonate structures not only lead to a variety of structures but also serve as charge separators with modulated catalytic activity. Interestingly, the lower dimensional transition metal phosphonate are often exciting for their strange magnetic behaviors and field-induced transitions. However, among plentiful stimulating properties of hybrid metal phosphonates, the electrocatalytic water splitting reaction remains less explored so far. With our continuous effort with metal phosphonates, herein we have isolated two new hybrid one-dimensional transition-metal phosphonate chain structures with templated TETA through a hydrothermal pathway (i.e., [H 2 TETA]­[M­(H 2 hedp) 2 ]·2H 2 O, where M = Co for I , Ni for II ; H 4 hedp = 1-hydroxyethane-1,1-diphosphonic acid; TETA = triethylenetetramine) for the investigation of their electrochemical behaviors toward OER and HER. The present study not only explores the potential of any low cost bifunctional OER/HER catalyst designed by organophosphonate ligands but also exposes a promising avenue to explore stable, efficient, and precious-metal-free lower-dimensional framework structures as electrocatalysts.…”
mentioning
confidence: 99%